Penerapan Pelaksanaan Going Concern Oleh Tim Kurator PT Star Prima (Dalam Pailit) - Dina Fiddaniah; Arief Suryono (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
In the Bankruptcy Law and PKPU, there are two steps in proposing a going concern, namely after the bankruptcy decision (solvent), which is regulated in Article 104 of the Bankruptcy Law and PKPU, and after insolvency, which is regulated in Article 179 paragraph (1) of the Bankruptcy Law and PKPU. This research uses an empirical juridical approach. Empirical juridical research is data that is first examined, namely secondary data, followed by research on primary data in the field or in the community. This research is descriptive empirical normative legal research. Types and sources of research data include primary data and secondary data consisting of primary and secondary legal materials. The approaches used in this research are the statute and case approaches. The research results show that the implementation of going concern carried out by the PT Star Prima Curator Team (in bankruptcy) is by the Bankruptcy Law and PKPU, namely 1) obtaining approval/permission from the supervisory judge and the creditors accepted, 2) proposed when the debtor is in a state of insolvency, 3) regularly 3 (three) months once reported to the supervising judge.